2022
DOI: 10.1002/suco.202100704
|View full text |Cite
|
Sign up to set email alerts
|

Study of shear‐thickening and shear‐thinning behavior in rheology of self‐compacting concrete with micro‐nano bubble

Abstract: This research investigated the effect of using micro-nano bubbles and superplasticizers on the rheology of self-compacting concrete (SCC). Eight mix designs were made with different values of 4-5.5 kg/m 3 of superplasticizer. For comparison, half of the mix designs were made with micro-nano bubbles, and the rest were made with tap water. Flowability, passing ability, and rheological tests were performed on all mixed designs. The results show that an increased rate of superplasticizer from 4 to 5 kg/m 3 improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Scholars worldwide have conducted relevant research on the effect of polycarboxylate superplasticizer on the performance of cement [20][21][22][23][24][25]. Ke et al [26] studied the effect of polycarboxylate superplasticizer on the fluidity, rheology, and thixotropic properties of a low water-to-binder ratio cement-silica mortar slurry, and found that it had obvious dispersion advantages for cementitious materials.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars worldwide have conducted relevant research on the effect of polycarboxylate superplasticizer on the performance of cement [20][21][22][23][24][25]. Ke et al [26] studied the effect of polycarboxylate superplasticizer on the fluidity, rheology, and thixotropic properties of a low water-to-binder ratio cement-silica mortar slurry, and found that it had obvious dispersion advantages for cementitious materials.…”
Section: Introductionmentioning
confidence: 99%